2017
DOI: 10.1021/acs.jpcc.6b11963
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Aggregation Mechanism of Gold Nanoparticles Triggered by a Globular Protein

Abstract: Gold nanoparticles (AuNPs) are advancing a number of areas. Meanwhile, the inevitable contact of AuNPs with surrounding biomolecules has been realized to “negatively” impact the nanoparticle (NP) function, biological environment, and even public health. Understanding the mechanisms of the NP–biomolecule interaction often leads to revealing the pathways toward the negative, deleterious effects. It is therefore essential to know the undesirable pathways so that these unwanted effects can be reduced by blocking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 88 publications
2
58
0
Order By: Relevance
“…At low protein concentration, only one or a few proteins weakly adhere to the NP on average, and protein–protein interactions are less likely to occur. Thus, each weakly bound protein molecule unfolds individually, and its linear polypeptide chain spreads across the surface and covers an area of several times its footprint in the folded state (Figure ) . The actual dimension of the footprint depends on the relative strength of the protein–surface interaction and the internal stability of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…At low protein concentration, only one or a few proteins weakly adhere to the NP on average, and protein–protein interactions are less likely to occur. Thus, each weakly bound protein molecule unfolds individually, and its linear polypeptide chain spreads across the surface and covers an area of several times its footprint in the folded state (Figure ) . The actual dimension of the footprint depends on the relative strength of the protein–surface interaction and the internal stability of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is PEG somehow disrupts the interaction of the protein with the substrate, which changes the surface charge of the hybrid and/or blocks the access pathway of substrates. Our recent work showed that T4L was able to trigger the aggregation of small AuNPs (14 nm) due to the positive surface charge . Therefore, AuNPs are effective sensors to probe T4L charges.…”
Section: Resultsmentioning
confidence: 99%
“…The details of polymer modification and polymer‐protein conjugation are provided in the SI. The AuNPs were prepared using a known procedure with minor modifications . UV spectra were obtained with the NanoDrop UV‐vis spectrophotometer (Thermo Scientific ND‐2000 C) at the Core Biology Facility of Department of Chemistry and Biochemistry, North Dakota State University (NDSU).…”
Section: Methodsmentioning
confidence: 99%
“…Static Light Scattering (SLS) was conducted on a Zetasizer Nano‐ZS (Malvern ZEN 3690, Malvern Instruments). A Varian E‐109 spectrometer fitted with a cavity resonator was used for all CW EPR studies . The typical sample concentration for our CW EPR studies was ∼100 μM.…”
Section: Methodsmentioning
confidence: 99%